UEM - campus e planos : formalizando a universidade planejada - Avanci, Renan Augusto (2016)
UEM - Campus and plans: formalizing the planned University is a dissertation that seeks by formal analyzes of two projects proposed in the territory of the State University of Maringá (UEM) a way of characterizing the campus that was idealized. The investigations about these plans have as objective to contribute to the comprehension of the projectual strategies proposed for the campus in Maringá, paying attention, specifically, to the formal systems of organization of the university territories that were so nationally and internationally discussed in the 60's. For so, the structure of this research fulfills, in its first stage an initial approach of the concept of university campus. From the north American creation to the portrait of the process of the national campus constitution by the projects of the University of Brazil (UB) and from the University of Brasilia (UnB) which were presented as relevant patriotic models. In the same way, we consider the following debates about the spatial architecture of the Brazilian campus having in mind a University Renovation of 1968 which proposed basic principles to the modernization of the academic teaching and consequently , of its physical ordering and planning. Based on this theoretical justification, in the next two stages we dedicated, in fact, to the study of project for UEM. In a first moment in a descriptive approach and, later, under an analytic condition. For the description and analyzes of these plans, we defined, in a broad way, six categories - physical area, implementation, sectorization, circulation, didactic edification in relation to the city - whose requirements were intrinsic to the formal characterization of the object studied. We understood in the end, that the campus that was planned and its final representations and attributes, contain recognitions of distinct formal systems of university space settings characterized by linear spatiality proposed in the first plan and spatiality in grid set in the second project.